Ingesting a bitter solution: The sweet touch to increasing short-term cycling performance - Etxebarria, N.; Ross, M. L.; Clark, B.; Burke, L. M. (International Journal of Sports Physiology and Performance, 2019)
Purpose: The authors investigated the potential benefit of ingesting 2 mM of quinine (bitter tastant) on a 3000-m cycling time-trial (TT) performance. Methods: Nine well-trained male cyclists (maximal aerobic power: 386 [38] W) performed a maximal incremental cycling ergometer test, three 3000-m familiarization TTs, and four 3000-m intervention TTs (~4 min) on consecutive days. The 4 interventions were (1) 25 mL of placebo, (2) a 25-mL sweet solution, and (3) and (4) repeat 25 mL of 2-mM quinine solutions (Bitter1 and Bitter2), 30 s before each trial. Participants self-selected their gears and were only aware of distance covered. Results: Overall mean power output for the full 3000 m was similar for all 4 conditions: placebo, 348 (45) W; sweet, 355 (47) W; Bitter1, 354 (47) W; and Bitter2, 355 (48) W. However, quinine administration in Bitter1 and Bitter2 increased power output during the first kilometer by 15±11 W and 21±10 W (mean±90% confidence limits), respectively, over placebo, followed by a decay of 34?±?32 W during Bitter1 and Bitter2 during the second kilometer. Bitter2 also induced a 11±13-W increase during the first kilometer compared with the sweet condition. Conclusions: Ingesting 2 mM of quinine can improve cycling performance during the first one-third of a 3000-m TT and could be used for sporting events lasting ~80 s to potentially improve overall performance.